Diurnal and Seasonal Dynamics of Solar‐Induced Chlorophyll Fluorescence, Vegetation Indices, and Gross Primary Productivity in the Boreal Forest. Issue 2 (16th February 2022) - Pierrat, Zoe; Magney, Troy; Parazoo, Nicholas C.; Grossmann, Katja; Bowling, David R.; Seibt, Ulli; Johnson, Bruce; Helgason, Warren; Barr, Alan; Bortnik, Jacob; Norton, Alexander; Maguire, Andrew; et al.
Abstract: Remote sensing of solar‐induced chlorophyll fluorescence (SIF) provides a powerful proxy for gross primary productivity (GPP). It is particularly promising in boreal ecosystems where seasonal downregulation of photosynthesis occurs without significant changes in canopy structure or chlorophyll content. The use of SIF as a proxy for GPP is complicated by inherent non‐linearities due to both physical (illumination effects) and ecophysiological (light use efficiencies) controls at fine spatial (tower/leaf) and temporal (half‐hourly) scales. To study the SIF‐GPP relationship, we investigated the diurnal and seasonal dynamics of continuous tower‐based measurements of SIF, GPP, and common vegetation indices at the Southern Old Black Spruce Site (SOBS) in Saskatchewan, CA over the course of two years. We find that SIF outperforms other vegetation indices as a proxy for GPP at all temporal scales but shows a non‐linear relationship with GPP at a half‐hourly resolution. At small temporal scales, SIF and GPP are predominantly driven by light and non‐linearity between SIF and GPP is due to the light saturation of GPP. Averaged over daily and monthly scales, the relationship between SIF and GPP is linear due to a reduction in the observed PAR range. Seasonal changes in the light responses of SIF and GPP are driven by changes in light use efficiency which co‐vary with changes in temperature, while illumination and canopy structure partially linearize the SIF‐GPP relationship. Additionally, we find that the SIF‐GPP relationship has a seasonal dependency. Our results help clarify the utility of SIF for estimating carbon assimilation in boreal forests. Plain Language Summary: Remote sensing can help us better understand plants' role in the global carbon cycle. In particular, a small light signal emitted by plants during photosynthesis, known as solar‐induced chlorophyll fluorescence (SIF), is a promising remotely sensed proxy for carbon uptake due to its strong relationship with gross primary productivity (GPP, ecosystem carbon assimilated during photosynthesis) when observed by satellite. Recent work at the leaf and tower‐scale has highlighted differences in the relationship between SIF and GPP, thereby raising questions over the utility of SIF for this purpose. We collect tower‐based SIF and GPP measurements from the southern end of the boreal forest to clarify their connection in boreal ecosystems. We find that temporal resolution is critical for understanding the nuances between SIF and GPP and that light and temperature effects complicate their relationship. Additionally, the relationship between SIF and GPP has a seasonal dependency that should be considered when using SIF. Taken together, our results suggest that SIF is a powerful tool for estimating carbon assimilation in boreal forests, but some key considerations need to be addressed for properly interpreting this faint signal. Key Points: Tower‐based solar‐induced chlorophyll fluorescence (SIF) closely tracks gross primary productivity (GPP) over two years in a mixed‐species boreal forest Light saturation of photosynthesis drives non‐linearity between SIF and GPP The SIF‐GPP relationship is seasonally variant due to dynamics between LUEF and LUEP